Deureuham dan Aktivitas Perdagangan Maritim di Samudera Pasai - Stanov Purnawibowo (Berkala Arkeologi Sangkhakala, 2009)
AbstractDeureuham of Samudera Pasai Kingdom is one of the fact of the past in line with commercial activity, especially in commercial maritime around the eastern coast of Northern Sumatera. As one of the official exchange rate at that time, deureuham of pasai inspired coinage in the Islam Kingdom in Malay Peninsula.